Haemolytic and co‐haemolytic (CAMP‐like) activity in dermatophytes. Issue 1 (5th December 2014) - Döğen, Aylin; Gümral, Ramazan; İlkit, Macit
Summary Dermatophytes are some of the most common fungal pathogens in both humans and animals. These fungi release enzymes (e.g., keratinases) that play roles in their pathogenesis. Little is known about their haemolytic and co‐haemolytic (CAMP‐like) activities; however, in bacteria, these components play significant roles in pathogenesis. This study characterised these two factors in 45 dermatophyte strains (representing the genera Arthroderma, Epidermophyton, Microsporum and Trichophyton) using Columbia agar (CA) supplemented with 5% bovine, ovine and equine erythrocytes. Haemolysis was best observed on CA supplemented with ovine erythrocytes followed by equine and bovine erythrocytes, while CAMP‐like reactions occurred using bovine and ovine but not equine erythrocytes. Haemolytic and CAMP‐like activities were best observed using ovine and bovine erythrocytes in CA in 44 and 38 strains at 7 and 3 days respectively. Most dermatophytes recovered from both symptomatic and asymptomatic lesions had haemolytic and CAMP‐like activities. We suggest that the haemolytic and CAMP‐like activities are not correlated with ecological characteristics, isolation sites or clinical manifestations of dermatophytic fungi. We also believe that this study has the potential to contribute to the existing literature on dermatophytes and dermatophyte pathogenesis.